2010
DOI: 10.1371/journal.pone.0011499
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles of Beta-Cell Enriched Tissue Obtained by Laser Capture Microdissection from Subjects with Type 2 Diabetes

Abstract: BackgroundChanges in gene expression in pancreatic beta-cells from type 2 diabetes (T2D) should provide insights into their abnormal insulin secretion and turnover.Methodology/Principal FindingsFrozen sections were obtained from cadaver pancreases of 10 control and 10 T2D human subjects. Beta-cell enriched samples were obtained by laser capture microdissection (LCM). RNA was extracted, amplified and subjected to microarray analysis. Further analysis was performed with DNA-Chip Analyzer (dChip) and Gene Set Enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
257
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 276 publications
(281 citation statements)
references
References 79 publications
21
257
2
1
Order By: Relevance
“…In accordance with previous studies [13,14], light microscopy revealed that the islets varied in terms of size, insulin-and glucagon-positive areas, and they either retained a normal architecture or instead displayed sparse architecture (ESM Fig. 2).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In accordance with previous studies [13,14], light microscopy revealed that the islets varied in terms of size, insulin-and glucagon-positive areas, and they either retained a normal architecture or instead displayed sparse architecture (ESM Fig. 2).…”
Section: Resultssupporting
confidence: 91%
“…In addition, in carefully performed examinations, morphological variations in type 2 diabetic islets have also been reported [13,14]. The present study confirms the presence of such alterations by the use of insulin immunocytochemistry and the measurement of fractional pancreatic beta cell area (a surrogate of beta cell mass) [10].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, the length of the culture period from isolation to molecular assessments may play a role [35], and, finally, the endocrine cell heterogeneity of the islets precludes the clear determination of the properties of the beta cells [36]. A possible solution to some of these problems is the use of beta cells from frozen pancreas samples, as obtained by laser capture microdissection [37,38]. Marselli et al [38] published a study comparing the transcriptomics of laser microdissected beta cells prepared from the pancreas of ten type 2 diabetic and ten non-diabetic organ donors.…”
Section: Islet Expression Of Cytokines and Chemokines In Type 2 Diabetesmentioning
confidence: 99%
“…A possible solution to some of these problems is the use of beta cells from frozen pancreas samples, as obtained by laser capture microdissection [37,38]. Marselli et al [38] published a study comparing the transcriptomics of laser microdissected beta cells prepared from the pancreas of ten type 2 diabetic and ten non-diabetic organ donors. The expression of genes encoding inflammatory and/or immunomodulatory mediators, and that of markers of inflammatory cells were evaluated.…”
Section: Islet Expression Of Cytokines and Chemokines In Type 2 Diabetesmentioning
confidence: 99%